Alternative measures to evaluate the impact of vocational rehabilitation services - Gibbs, Ernest W. [Verfasser] (My University, 1990)
"This article examines the relationship between the receipt of vocational rehabilitation services and the length of time a person is employed and unemployed. Using data from the Virginia Department of Rehabilitative Services and the Virginia Employment Commission, the employment histories of 2,536 participants who were successfully rehabilitated in fiscal year 1982 were compared with other persons with disabilities who did not receive any vocational rehabilitation services. Stratifying individuals by age, education, race, gender, and disabling condition, the hazard rate model yielded results that suggest longer periods of employment and shorter periods of unemployment in relation to the receipt of vocational rehabilitation services." (author's abstract) ((en)) In dem Beitrag wird untersucht, wie sich die Teilnahme an beruflichen Rehabilitationsmassnahmen auf die Arbeitsmarktchancen auswirkt. Daten über den beruflichen Werdegang von 2536 Rehabilitanden, die ihre Rehabilitation im Jahre 1982 in Virginia/ USA erfolgreich beendet haben, werden mit Daten von Behinderten verglichen, die keine Rehabilitationsleistungen erhalten haben. Die Ergebnisse belegen längere Phasen der Erwerbstätigkeit und kürzere Phasen der Arbeitslosigkeit bei rehabilitierten Personen. (IAB)
Alternative Messmethode für die Auswirkungen von beruflichen Rehabilitationsmassnahmen
Keywords: G 1.3.3.4 Wiedereingliederung; G 2.3.1 Arbeitsteilung & -organisation; G 1.2 Arbeitsmarkt; Berufliche Rehabilitation; Erfolgskontrolle; Menschen mit Behinderung; Erwerbstätigkeit; Arbeitslosigkeit; Quantitative Angaben